Effect of inclusion levels of dried distillers grains with solubles (DDGS) on productivity and egg quality of Hy-Line Brown® laying hens - Castiblanco, F.; Paz, P. E.; Valdivié, M.; Martínez, Y. (Cuban Journal of Agricultural Science, 2021)
The effect of four levels of inclusion of dried distillers grains with solubles on the productive performance and egg quality of Hy-line Brown® laying hens was evaluated. A total of 140 animals were distributed in four treatments, according to a completely randomized design, for 10 weeks. Seven repetitions per treatment and five birds per repetition were established. The treatments consisted of a control diet and the inclusion of 10, 15 and 20 % of dried distillers grains with solubles. The inclusion of 0 and 10 % promoted (P <0.05) laying intensity and mass conversion with respect to 15 and 20 %. In addition, diets with dried distillers grains with solubles increased (P <0.05) feed intake, nutrients and metabolizable energy, as well as shell thickness and yolk color (P <0.05), without notable changes (P> 0.05) for albumen height, Haugh unit and resistance to shell rupture. It is recommended the inclusion of 10 % of dried distillers grains with solubles in partial substitution of corn and soybean meal in diets intended for Hy-line Brown® laying hens. Key words: distillery byproducts, laying hens, productive indicator, egg external and internal quality